Neonatal protein kinase C zeta expression determines the neonatal T-Cell cytokine phenotype and predicts the development and severity of infant allergic disease - D'Vaz, N.; Ma, Y.; Dunstan, J.; Lee-Pullen, T.; Hii, C.; Meldrum, S.; Zhang, Guicheng; Metcalfe, J.; Ferrante, A.; Prescott, S. (2012)
Background - Previous studies have demonstrated that reduced T-cell protein kinase C zeta (PKCζ) expression is associated with allergy development in infants born to atopic mothers. This study examined whether this relationship extends to a general population and addressed the basis for the association. Methods - A flow cytometry assay was developed for the measurement of T-cell PKCζ levels in PBMC, cord blood mononuclear cell and whole blood. Cord blood T-cell PKCζ levels were measured in 135 neonates, and allergic disease was evaluated by skin prick test and clinical examination at 12 months of age. Results - Allergic children (particularly those with eczema) had significantly lower neonatal T-cell PKCζ expression than nonallergic children (P < 0.001). PKCζ levels predicted allergic disease with optimal specificity of 86% and sensitivity of 54%. The sensitivity was increased in the children of allergic mothers, who had significantly lower PKC levels than the children of nonallergic mothers. Cord blood PKCζ levels did not affect T-cell maturation in culture as assessed by CD45RA/RO expression, but low PKCζ expression was associated with reduced capacity for IFNγ production by matured T cells. Low cord blood PKC expression was further associated with increased IL-13 responses at 6 months. Conclusions - The findings suggest a potential role for the use of PKCζ levels in cord blood T cells as a presymptomatic test to predict allergy risk in children, particularly offspring of allergic mothers, and that the basis of this relationship is related to cytokine patterns in mature T cells.